PERUBAHAN PERILAKU KONSUMTIF MASYARAKAT PASCA ISU RESESI EKONOMI GLOBAL TAHUN 2023 - Nur Farida; Lelli Kisdayanti; Nur Aini Anisa; Syamsul Arifin (Journal of Innovation Research and Knowledge, 2024)
In 2023, the World Bank in its report entitled "Is a Global Recession Imminent?" predicts that there will be a global economic recession, which is also likely to occur in Indonesia. The purpose of this study is to analyze the readiness of the community to face the threat of a global economic recession, one of which is from changes in consumptive behavior towards goods or services that are not primary needs. The method in this article is a qualitative research method with data collection techniques through interviews with several informants with different professions and income levels. Based on the results of the discussion in this article, it can be concluded that: There is a change in consumptive behavior in society after the issue of the global economic recession in 2023